2018
DOI: 10.1101/254524
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic contribution to ‘theory of mind’ in adolescence

Abstract: Difficulties in 'theory of mind' (the ability to attribute mental states to oneself or others, and to make predictions about another's behaviour based on these attributions) have been observed in several psychiatric conditions. We investigate the genetic architecture of theory of mind in 4,577 13-year-olds who completed the Emotional Triangles Task (Triangles Task), a first-order test of theory of mind. We observe a small but significant female-advantage on the Triangles Task (Cohen's d = 0.19, P < 0.01), in k… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…First, we showed that our individuals with ASD show differences in the SC measures (Eyes Task, BES, EQ, and A‐ToM Task) used in this study, compared to TD individuals. This result is in line with the more recent literature (Mazza et al, ; Warrier & Baron‐Cohen, ), and it confirms that SC difficulties are a central feature in ASD individuals. For this reason, it has become important to understand how these abilities interact.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…First, we showed that our individuals with ASD show differences in the SC measures (Eyes Task, BES, EQ, and A‐ToM Task) used in this study, compared to TD individuals. This result is in line with the more recent literature (Mazza et al, ; Warrier & Baron‐Cohen, ), and it confirms that SC difficulties are a central feature in ASD individuals. For this reason, it has become important to understand how these abilities interact.…”
Section: Discussionsupporting
confidence: 92%
“…We built two separate networks of SC components, one for ASD and one for TD, in order to map the interacting associations among the components that characterize this construct. Indeed, the SC construct can be defined as a complex network in which interacting components, such as ToM, emotion processing, empathy, self‐processing, and social identity, influence each other (Happé & Frith, ; Warrier & Baron‐Cohen, ). Individuals with ASD are characterized by a delay in the development of SC competencies (Mazza et al, ; Pino et al, , ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The leading SNP and the other 21 SNPs in high linkage disequilibrium with it are near LRRN1, which is highly expressed in brain tissue 17 . In a separate study, Warrier and Baron-Cohen 18 also investigated the genetics of cognitive empathy using data from the Avon Longitudinal Study of Parents and Children, a prospective birth cohort study (ALSPAC, see below). Among teenagers, no GWA significant signal was identified, and SNP-based heritability was negligible (0.13%, p = 0.16).…”
mentioning
confidence: 99%